KAJIAN DAMPAK PENDANAAN KARBON DALAM PEMBANGUNAN DAN OPERASIONAL PEMBANGKIT LISTRIK TENAGA UAP (PLTU) BERBAHAN BAKAR BATUBARA DENGAN TEKNOLOGI ULTRASUPERCRITICAL DI INDONESIA - Restu Adiati, Ririn
Indonesia today facing the lack of electricity condition. Acceleration program to develop 35.000 MW of electricity implemented by government yields problems such as very large investment needs and an increase of carbon emission. PT. PLN (Persero) planned to built 1.000 MW coal power plant using Ultra-supercritical (USC) technology. This technology generates better efficiency and lower carbon emission in coal power plant, better than Subcritical (Sub) technology which is currently used in Indonesia. Carbon emission reduction produced by USC will be used to gain carbon funding.